Economic valuation of farm animal genetic resources: Methods and applications to indigenous cattle in Kenya - Ruto, E.S.K. (University of Newcastle, 2004)
There is increasing global concern about the potential long term consequences of loss of domestic animal diversity. International agreements such as the Convention on Biological Diversity encourage the design of policies that convey economic incentives for conservation of genetic resources employed in agriculture. Of particular interest is the situation in developing countries where on one hand, livestock make the greatest contribution to human livelihoods and food security while on the other, genetic erosion has placed many adapted breeds that survive well in low input agriculture and extreme environments, typical of these countries, at risk of loss. An important goal is the development of policies and strategies for conservation and sustainable utilisation of these resources. Economic valuation tools for farm animal genetic resources (AGR) would contribute to this goal by providing information for decision making. It is from this background that this study, with special reference to indigenous cattle in Kenya, focuses on the nature of values associated with AGR and the methodological approaches that can be used to assign value, as a prerequisite to improved understanding of some of the forces that are driving their decline and designing well targeted economic incentives for their conservation and sustainable management.